2020
DOI: 10.1186/s12903-020-1042-8
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: a possible implication of Candida as an etiologically endogenous pathogen for oral lichen planus

Abstract: Background: The aim of this study was to investigate the prevalence and genotypic profiles of Candida albicans in patients with oral lichen planus (OLP). Materials and methods: Positive rates and genotypic profiles of Candida albicans strains from OLP patients and healthy controls were analyzed. Random amplified polymorphic DNA and internal transcribed spacer of ribosome DNA polymerase chain reactions were used to sequence the DNA of these strains, and then their genetic similarity was measured using BLAST, UI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Probable genotypic mutations of C. albicans in the occurrence and development of OLP (Fig. 1 ) were illustrated in previous researches [ 5 , 6 ]. Further studies about phase transformation of C. albicans in OLP progression have been conducted.…”
Section: Introductionsupporting
confidence: 54%
“…Probable genotypic mutations of C. albicans in the occurrence and development of OLP (Fig. 1 ) were illustrated in previous researches [ 5 , 6 ]. Further studies about phase transformation of C. albicans in OLP progression have been conducted.…”
Section: Introductionsupporting
confidence: 54%
“…In contrast, Odds et al described in 1989 that the yeast C. albicans is unequivocally associated with OLP in 37% of the patients; the authors also reported that, apart from C. albicans (Jacobsen et al 2008 ), there were additional yeast species occasionally present in the lesions, including C. tropicalis , C. pintolopesii , Torulopsis glabrata , and Saccharomyces cerevisiae . However, a more recent study (Hong et al 2020 ) indicated that the presence of C. albicans in OLP lesions is not as common as previously believed, reporting a prevalence of only 18.87 and 18.75% in non-erosive and erosive varieties of the disease, respectively, while the prevalence of the yeast is 7.92% in healthy people. The conclusions from the latter report indicate that although the disease appears to involve only a minor dysbiosis, at least concerning C. albicans , the yeast only appears in a small percentage of people suffering from OLP; this suggests a role for the pathogenic yeast as a secondary colonizer, as it does not fulfill the conditions reflected in Koch’s postulates to be considered as the origin of the disease.…”
Section: Fungi Associated With Oral Lichen Planusmentioning
confidence: 88%
“…However, these two researchers examined the samples in two ways. In one case, they examined the presence of hypha by potash staining, and in the second case, they examined the invasion of Candida in the biopsy samples of patients [ 15 , 16 ]. He et al in 1 of 43 biopsies and Krogh in none of the 19 samples showed Candida invasion.…”
Section: Discussionmentioning
confidence: 99%
“…He et al in 1 of 43 biopsies and Krogh in none of the 19 samples showed Candida invasion. He et al reported 10 positive samples with potash staining and Krogh 37% of the samples positive [ 16 ].…”
Section: Discussionmentioning
confidence: 99%